Sistem Aplikasi Pencatatan Penjualan Berbasis Web Pada Konveksi Tas Latif Dengan Metode Design Thinking - Muhammad Khaesar Juniardi; Nanda Kamila Azzahra; Wahyu Eka Candra; Joko Priambodo (CV. Shofanah Media Berkah, 2025)
This internship was carried out at a Konveksi Tas Latif located at Jl. Kota Bambu Utara RT 11 RW 1 No. 17, Kota Bambu Utara, Kecamatan Palmerah, Kota Jakarta Barat 11420. The purpose of this internship is to design and develop a web-based sales recording application for the bag convection business. Until now, the transaction and sales recording process has been conducted manually, which can potentially lead to recording errors, data loss, and difficulties in compiling sales reports.The system development method was conducted through field observation, interviews with related parties, and the waterfall approach, which includes requirements analysis, system design, implementation, and testing. The system was developed using the PHP programming language and MySQL database, enabling integrated and real-time management of transaction and sales data.The result of this internship is a web-based sales recording application capable of automatically recording sales transactions, storing customer and product data, and generating sales reports automatically, both daily and monthly. This system provides convenience in business operations, improves work efficiency, and minimizes the risk of data loss. With the implementation of this system, it is expected that the business processes in the bag convection enterprise will become more effective, organized, and supportive of future business growth.